Innovation and economic development : a microeconomic perspective - Johannessen, Jon-Arild (Routledge studies in the economics of innovation., 2026)
Microeconomic theorists have largely excluded entrepreneurship and innovation from their theoretical analyses and models. In the existing literature, innovative entrepreneurs are hardly mentioned at all, yet it is precisely these entrepreneurs who, through their establishment of innovation-based start-ups, for example, start-ups based on technological innovations, create economic growth and help promote prosperity worldwide. The most recent examples from the digital revolution alone, such as Microsoft, Apple, and TikTok, speak to the importance of innovative entrepreneurship. This book addresses the lack of microeconomic theory concerning the role of innovation as a driver for economic development and explores the topic from multiple perspectives: innovative entrepreneurship, competence, productivity, automation, and the institutional framework.By analysing these five pillars, the book provides a broad idea of how these interactions all impact how the innovation economy continues to thrive. The book also describes the application of theory to real life by providing practical and real-life examples and case studies. It demonstrates the need to foster the spirit of innovation and entrepreneurship for sustainable development as a key driver of uninterrupted industrial development. It also highlights the critical gap in conventional economic models, which reduce everything to a single number and fail to analyse how innovation shapes both economic structures and the education systems and policies needed to adapt to them. By incorporating systems thinking and evolutionary economics, the book offers a multidimensional analysis of the innovation economy.This broad perspective enhances its theoretical depth and widens its appeal to scholars and researchers across various disciplines. Its practical approach also makes the book relevant to policymakers, educators, and practitioners.